Market Liberals at a Crossroads in Post-Gezi Turkiye: Making Sense of a Framing Dispute - Mustafa Cüneyt Özşahin; H. Bahadır Akın; Şeyma Akın (Journal of Economy Culture and Society)
The Gezi protests were a watershed moment for market liberals since it triggered inter-movement and intra-movement schisms. A flagship institution of market liberals, Liberal Düşünce Topluluğu (the Association of Liberal Thought) underwent such a schismatic process and, consequently, new market-liberal organizations arose from the schism, which was characterized by a frame dispute with the ALT over the policies pursued by the incumbent government, Justice and Development Party (JDP). The framing dispute between the two factions occurred along the lines of securing democracy versus the restriction of state power. This study delineates the root causes of the framing dispute between market liberals. To this end, two factors are proposed to account for it within the context of this paper. These two factors can be encapsulated as the growing conservative/liberal division among market liberals and entrenched interpersonal patronage networks within political circles which is closely related to the changing nature of government-civil society relations in Turkey. Drawing from semi-structured interviews, publications of market liberals, and a good number of secondary sources, we aim to shed light on the rift within market liberals in post-Gezi Turkey.